2017
DOI: 10.1007/s00406-017-0841-7
|View full text |Cite
|
Sign up to set email alerts
|

Remnants and changes in facial emotion processing in women with remitted borderline personality disorder: an EEG study

Abstract: According to longitudinal studies, most individuals with borderline personality disorder (BPD) achieve remission. Since BPD is characterized by disturbed emotion recognition, this study investigated behavioral and electrophysiological correlates of facial emotion classification and processing in remitted BPD. 32 women with remitted BPD (rBPD), 32 women with current BPD (cBPD), and 28 healthy women (HC) participated in an emotion classification paradigm comprising blends of angry and happy faces while behaviora… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
13
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 40 publications
3
13
0
Order By: Relevance
“…Our data suggest that these alterations still exist after a remission from acute BPD symptoms, even if individuals achieve relatively high levels of social and vocational functioning. Our findings are in line with those reported by Schneider et al [32] in symptom-remitted BPD and support the assumption that subtle impairments in the recognition of positive social cues constitute a trait-like feature in BPD.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Our data suggest that these alterations still exist after a remission from acute BPD symptoms, even if individuals achieve relatively high levels of social and vocational functioning. Our findings are in line with those reported by Schneider et al [32] in symptom-remitted BPD and support the assumption that subtle impairments in the recognition of positive social cues constitute a trait-like feature in BPD.…”
Section: Discussionsupporting
confidence: 93%
“…So far, experimental studies on facial emotion processing in symptom-remitted BPD patients are sparse. One recent study used a forced-choice task to investigate how symptom-remitted BPD patients categorize ambiguous emotional faces that were blends of angry and happy facial features [32]. While the patients categorized the stimuli in a manner comparable to healthy participants, both processing times and the P300 component of event-related potentials indicated alterations during the evaluation of facial stimuli with predominantly positive facial features.…”
Section: Introductionmentioning
confidence: 99%
“…Results remain inconclusive among adolescent patients with BPD with some authors reporting a similar negativity bias as in adult patients [24, 25], while others failed to find differences in emotion recognition [26] or even found an impaired sensitivity to facial emotions [27]. First data from our own group point to a reduced threat hypersensitivity in former patients with BPD, i.e., individuals who were diagnosed with BPD, but who did not fulfill more than 3 BPD criteria in the last 2 years [28]. Unlike patients with a current diagnosis of BPD, these patients with BPD in remission did not significantly differ from healthy participants in the recognition of faces displaying subtile signals of facial anger.…”
Section: Recent Behavioral Findingsmentioning
confidence: 71%
“…The study also revealed the possible drawbacks of such an early hypersensitivity to potentially threatening information, since reduced temporo-occipital N170 and centroparietal P300 amplitudes suggest impairments in subsequent stages of structural as well as categorical and contextual processing of facial information. Interestingly, Schneider et al [28] could not find such alterations in P100 and N170 amplitudes in patients with BPD in remission suggesting that a “remission” of the behavioral negativity bias may be related to a normalization of very early stages of face processing. While increased early hyperresponsivity may hence be regarded as a stress- or arousal-related state marker for symptom severity or illness, reductions in P300 amplitudes persisted in patients with BPD in remission and could thus reflect a trait-like disorder-related marker for deficits in cognitive control and other more stable aspects of BPD.…”
Section: Neurobiological Correlatesmentioning
confidence: 99%
“…Thus, training in attentional skills may qualify as a significant treatment tool for BPD, e.g., using tasks similar to “Find a Face” game [31], which encourages patients to focus attention on friendly, trustworthy faces which compete with negative, rejecting, or threatening faces. Other computerized programs which are currently tested in BPD instruct patients to carefully scan facial emotions instead of rapidly evaluating them in a holistic manner, reducing automatic, rough preconscious processing of social cues [32], has been reported from studies in patients with BPD [33]. A more adaptive attentional processing of social cues could fulfil an important requirement for subsequent cognitive interventions that aim to modify cognitions by reinstructing reappraisal strategies.…”
Section: Clinical Implications and Suggestions For Further Researchmentioning
confidence: 99%